2022
DOI: 10.1186/s13014-022-02062-x
|View full text |Cite
|
Sign up to set email alerts
|

30-day mortality in patients treated for brain metastases: extracranial causes dominate

Abstract: Background Established prognostic models, such as the diagnosis-specific graded prognostic assessment, were not designed to specifically address very short survival. Therefore, a brain metastases-specific 30-day mortality model may be relevant. We hypothesized that in-depth evaluation of a carefully defined cohort with short survival, arbitrarily defined as a maximum of 3 months, may provide signals and insights, which facilitate the development of a 30-day mortality model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“… 6 , 7 , 17 , 18 , 19 In 1 recent study inclusive of 100 patients treated with radiation for brain metastases, extracranial disease progression (measured by blood test results and imaging) was a significant predictor for 30 DM. 16 Consistent with this observation, a lower KPS score and extracranial disease were associated with 30-DM in our analysis. These factors highlight the importance of evaluating a patient's intracranial disease in the context of their systemic progression and performance status.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“… 6 , 7 , 17 , 18 , 19 In 1 recent study inclusive of 100 patients treated with radiation for brain metastases, extracranial disease progression (measured by blood test results and imaging) was a significant predictor for 30 DM. 16 Consistent with this observation, a lower KPS score and extracranial disease were associated with 30-DM in our analysis. These factors highlight the importance of evaluating a patient's intracranial disease in the context of their systemic progression and performance status.…”
Section: Discussionsupporting
confidence: 89%
“… 4 , 13 , 14 , 15 One recent study of patients with brain metastases from any primary site reported a 30-DM of 28%. 16 We observed a lower rate of 30-DM in our cohort, possibly owing to inclusion of those receiving SRS to limited intracranial metastases, representing a population with a better prognosis. The 30-DM rate for those receiving SRS was 7.7%, suggesting that patients are appropriately being selected for SRS at our center.…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, we had access to a broad set of baseline parameters and were therefore able to extend the knowledge provided by previous, otherwise similar studies. Patients with brain metastases, a small subgroup in the present study, might represent a special population, if treated to the brain [ 17 ] rather than skeletal metastases after previous brain-directed therapy. Our group’s previous work [ 17 ] resulted in different predictors of 30-day mortality after treatment for brain metastases (n = 100 patients) than those identified in the present bone metastases study, e.g., number of brain metastases and primary tumor control.…”
Section: Discussionmentioning
confidence: 99%
“…While the recent meta-analysis by Kutzko et al 18 identified a 30 day mortality following PRT benchmark of 16%, given that several studies globally have reported 30-day mortality rates following PRT as low as 5-10% 24,25,30 we encourage individual RT centres throughout Australia and New Zealand to strive for as low a rate as possible taking into account each site's individual patient case mix, while being mindful of the potential for underutilisation or overutilisation of PRT based on the adopted benchmark.…”
Section: Public Versus Private Rt Facilitiesmentioning
confidence: 99%